To join or not to join - Huang, Yue. (2011)
In the recent year, a large amount of work has been done and researched on XML database. XML has quickly adopted as the industry standard for storing and exchanging data, especially in the web. However, the usability of such databases has been largely ignored. XML database are consumed by not only the database experts but also by many types of user, some of them are not technical people with database specialization. It’s hard for them to use, modify and query the XML database. Therefore, there is a need of producing a more user-friendly, semantic query language to exploit XML database. For example, the biologist has little knowledge about database. However, they have the needs to query large biology database when they are doing the biological research. It’s very necessary for computer engineers to create a user-friendly XML database system for people with no database background knowledge.